A Note on Derivative of Sine Series with Square Root - Sergiusz Kęska (Abstract and Applied Analysis)
Chaundy and Jolliffe proved that if an is a nonnegative, nonincreasing real sequence, then series ∑ansinnx converges uniformly if and only if nan⟶0. The purpose of this paper is to show that if nan is nonincreasing and nan⟶0, then the series fx=∑ansinnx can be differentiated term-by-term on c,d for c,d>0. However, f′0 may not exist.